Efektifitas Pembiayaan Akad Musyarakah Bagi Pelaku UMKM pada Bank Tabungan Pensiunan Nasional (BTPN) Syariah - Dwi Yulia Hariyani; Sunarsih Sunarsih; Hammad Farobi Syahuda (MAMEN: Jurnal Manajemen, 2026)
MSMEs play a vital role in the national economy, yet they still face a major obstacle, namely limited business capital. Musharaka financing in Islamic banking offers a solution, as it implements the principles of partnership and profit-sharing. This study aims to analyze the effectiveness of musharaka financing for Micro, Small, and Medium Enterprises (MSMEs) at the National Pension Savings Bank (BTPN) Syariah in Central Lombok Regency. This study employed a qualitative approach with descriptive analytical methods through interviews with five MSME customers receiving musharaka financing and one BTPN Syariah employee. The results indicate that musharaka financing is effective in increasing customers' access to capital, income, business stability, and business sustainability. This effectiveness is supported by a fair profit-sharing system, business mentoring, financial training, and regular monitoring by the bank. However, obstacles remain, such as low transparency in business reports, weak financial records, and the risk of moral hazard due to information asymmetry between the bank and customers. Therefore, strengthening mentoring, financial literacy, and monitoring systems are important factors in increasing the effectiveness of musyarakah financing for MSMEs.